Laboratory Officer Compliance with Standard Operating Procedures at the Laboratory Installation of Grandmed Lubuk Pakam Hospital Based on the Quality of Laboratory Examination Results - Ajeng Prahesti; Ahmad Hafizullah Ritonga; Novita Br Ginting Munthe (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Standard Operating Procedures (SOP) serve as work guidelines to ensure the quality and consistency of laboratory services. Laboratory personnel compliance with SOPs is essential to minimize errors in the pre-analytical, analytical, and post-analytical stages that may affect the quality of examination results. This study aimed to analyze laboratory staff compliance with SOP and its relationship with the quality of laboratory examination results at Grandmed Hospital, Lubuk Pakam. This research used a quantitative approach with an analytical cross-sectional design. The population consisted of all laboratory personnel at Grandmed Hospital Lubuk Pakam, totaling 30 people, selected using total sampling. Data were collected through questionnaires and observation, then analyzed using descriptive analysis and the Chi-Square test. The results showed that the level of laboratory personnel compliance with SOPs was in the high category. The Chi-Square test indicated that examination result quality, individual factors, and organizational factors had a significant relationship with SOP compliance (p < 0.05), while environmental factors showed no significant relationship (p > 0.05). In conclusion, compliance with SOPs plays an important role in maintaining the quality of laboratory examination results. Therefore, regular supervision, periodic SOP training, and continuous evaluation are needed to improve the quality of laboratory services